Optical and electrical properties of ZnO thin films grown by sol-gel method - Bała, W.; Zorenko, Yu.; Savchyn, V; Voznyak, T.; Paprocki, K.; Popielarski, P.; Szybowicz, M. (Видавництво Львівської політехніки, 2012)
The ZnO thin films have been produced on p-type Si by the dip-coating method and after deposition were heated at different temperatures in the range from 650K to 850K. The photoluminescence (PL) and cathodoluminescence (CL) measurements were carried out at temperature range 12K-350K. I-V, C-V, Q-DLTS measurements were performed on the Al/ZnO/Si/Al structures at different temperatures. The electrical response of grains, grain boundaries, and contacts of the ZnO film was obtained.
Keywords: zinc oxide; thin films; sol-gel method; luminescence; raman spectra